Individual and systems-related factors associated with heart failure self-care: a systematic review - Carolyn Kleman; Stephanie Turrise; Heidi Winslow; Omar Alzaghari; Barbara J. Lutz (BMC, 2024)
Abstract Background Heart failure (HF) is a prevalent condition worldwide. HF self-care is a set of behaviors necessary for improving patient outcomes. This study aims to review and summarize the individual and system-related factors associated with HF self-care published in the last seven years (Jan 2015 - Dec 2021) using the Socioecological Model as a review framework. Methods An experienced nursing librarian assisted authors in literature searches of CINAHL Plus with Full Text, Ovid Nursing, PsychINFO, and PubMed databases for peer-reviewed descriptive studies. Inclusion criteria were HF sample with self-care as the outcome variable, and a quantitative descriptive design describing individual and/or system-level factors associated with self-care. Exclusion criteria were interventional or qualitative studies, reviews, published before 2015, non-English, and only one self-care behavior as the outcome variable. The search yielded 1,649 articles. Duplicates were removed, 710 articles were screened, and 90 were included in the full-text review. Results A subset of 52 articles met inclusion and exclusion criteria. Study quality was evaluated using modified STROBE criteria. Study findings were quantitated and displayed based on socioecological levels. Self-care confidence, HF knowledge, education level, health literacy, social support, age, depressive symptoms, and cognitive dysfunction were the most frequently cited variables associated with self-care. Most factors measured were at the individual level of the Socioecological Model. There were some factors measured at the microsystem level and none measured at the exosystem or macrosystem level. Conclusion Researchers need to balance the investigation of individual behaviors that are associated with HF self-care with system-level factors that may be associated with self-care to better address health disparities and inequity.